Seroprevalence of Bordetella pertussis among vaccinated and unvaccinated pregnant women and newborn infants in a university hospital of Buenos Aires - Bosch, Juan J. (2017)
INTRODUCTION:Pertussis is a highly contagious disease caused by Bordetella pertussis. It poses a high morbidity and mortality rate, especially among infants younger than 6 months old. In Argentina, pertussis incidence and mortality have increased over the past three decades.OBJETIVE:To establish Bordetella pertussisantibody titers among pregnant women in their third trimester and among newborn infants, as measured in cord blood.METHODS:This was an observational, cross-sectional study. The study started in 2011; at that time, pertussis vaccination was not mandatory for pregnant women as per the national immunization schedule, only optional. Maternal antibodies were measured in the last trimester of pregnancy for women and in cord blood for newborn infants. Antibody titers were determined using Abcam´s anti-Bordetella pertussis toxin (PT) IgG in vitro ELISA kit. The χ² test was used to compare prevalence rates.RESULTS:The study included 111 mother-newborn infant dyads; 35 infants from unvaccinated mothers (before the introduction of the vaccine) and 76 from vaccinated mothers. Positive IgG antibodies were found in 92% (70/76) of infants born from vaccinated mothers whereas 100% (35/35) of infants born from unvaccinated mothers had negative results for antibodies; p < 0.001.CONCLUSION:In the vaccinated population of this study, 92% of infants had positive IgG antibodies. This study supports the need for maternal immunization against Bordetella pertussis to provide protection to newborn infants.